A PROTAGONIST CHARACTERISTIC OF RAMONA AND BEEZUS MOVIE - DEWI ASIA; IKA TRISNANTASARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2016)
This research is conducted to investigate the protagonist character of Ramona in the movie entitled Ramona and Bezuss. Commonly, the attitude of the children in third elementary school is naughty and annoying, but on the other hand, the director asked the audience to think otherwise by following, imagining and entering the children world. Therefore, it is interesting to analyzing the protagonist character in this movie since Ramona is in the capable family. The researcher use descriptive-qualitative method in conducting the research. Meanwhile, psychological and sociolinguistics is applied as the frame of the research. The source of the data is gained from the dialogue script of this movie. The researcher obtained some theory from psychological part such as cognitive theory, problem-solving, and the solving problem used ZDP (zone of proximal development), while in sociolinguistic the researcher found baby talk said by Ramona. This research is expected to give better knowledge about how to take care of the children correctly and try to understand the children world based on their point of view. In addition, the researcher expects the other researcher who is interested in baby talks’ based on the sociolinguistic theory to use this research as a reference.